Strategi Kebudayaan Ketua Program Studi Dalam Membentuk Performa Mutu Lembaga Pendidikan Islam - Nurdin, Muh Nur Islam; Sumedi, Sumedi (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
This study aims to analyse the cultural leadership strategies of the Head of the Master of Islamic Education Management (MMPI) Study Programme at UIN Sunan Kalijaga Yogyakarta in shaping the institution's quality culture. The background of this study stems from the Head of Study Programme's success in bringing MMPI to achieve ‘Excellent’ accreditation within one year, even though the study programme is still relatively young. This research uses a qualitative approach with an ethnographic design according to James P. Spradley (1979), which is relevant for exploring the value systems, norms, and habits that shape the academic culture of the institution. The research setting was in the MMPI programme environment with participants selected purposively, consisting of the Head of the Programme, the Secretary of the Programme, lecturers, educational staff, and students. Data were collected through participatory observation, semi-structured in-depth interviews, and documentary studies, then validated through triangulation of sources, techniques, and time. Data analysis was conducted interactively using the Miles and Huberman model, which included reduction, presentation, and drawing and verification of conclusions, accompanied by cultural meaning interpretation based on Spradley's ethnographic framework. The research results revealed three main cultural strategies: (1) building family traditions and work consistency, (2) displaying managerial exemplary behaviour that fosters trust and collective motivation, and (3) fostering a culture of quality through reflective and evaluative habits. These strategies create a collaborative academic climate, strengthen the cultural identity of the institution, and have a tangible impact on improving the academic quality performance of the MMPI at UIN Sunan Kalijaga.